XMapDB-Sim: Performance Evalaution on Model-based XML to Relational Database Mapping Choices - Haw Su-Cheng; Emyliana Song; Nur Amirah Azhar; Aisyah Amin (Institute of Advanced Engineering and Science, 2017)
XML has emerged as the standard for information representation over the Internet. However, most enterprises today have long secured the use of relational databases. Thus, it is crucial to map XML data into relational data to provide seamless integration between these database infrastructures. Many mapping techniques have been proposed, yet, none has provides a unified view on these techniques. Ultimately, understanding how these techniques work is important especially if one needs to decide which technique to adopt in their organization. This paper (i) reviews on some existing model-based mapping schemes focusing on how the mapping technique works, the advantages and the disadvantages, (ii) present the simulation engine to evaluate the performance of selected mapping schemes, (iii) highlight the future direction of the related area.